2009
DOI: 10.1158/1078-0432.ccr-08-3179
|View full text |Cite
|
Sign up to set email alerts
|

Detection of KRAS Oncogene in Peripheral Blood as a Predictor of the Response to Cetuximab Plus Chemotherapy in Patients with Metastatic Colorectal Cancer

Abstract: Purpose: Previously we developed membrane-arrays as a promising tool to detect circulating tumor cells (CTC) with KRAS oncogene in patients with malignancies.This study was conducted to determinate the predictive values of CTCs with KARS mutation by membrane-arrays for metastatic colorectal cancer patients treated with cetuximab plus chemotherapy. Experimental Design: Seventy-six metastatic colorectal cancer patients receiving cetuximab plus FOLFIRI or FOLFOX-4 chemotherapy were enrolled. KRAS mutation status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 27 publications
5
57
0
Order By: Relevance
“…27 Few studies have explored in small series of mCRC patients the correlation between KRAS mutational status in primary or metastatic tumor and in CTCs, revealing further mutational discordance, possibly complicating the selection of patients candidate for anti-EGFR treatments. [28][29][30][31][32][33] Our results confirm a divergent KRAS status in a large proportion of cases, highlighting that KRAS wild-type CTCs are frequently detected in peripheral blood of patients harboring mutated primary tumors. As potential mechanism to explain the relative prevalence of wild type KRAS CTCs, 34 the generation of hypoxia in large advanced tumors or induced by treatments has been evoked.…”
Section: Discussionsupporting
confidence: 71%
“…27 Few studies have explored in small series of mCRC patients the correlation between KRAS mutational status in primary or metastatic tumor and in CTCs, revealing further mutational discordance, possibly complicating the selection of patients candidate for anti-EGFR treatments. [28][29][30][31][32][33] Our results confirm a divergent KRAS status in a large proportion of cases, highlighting that KRAS wild-type CTCs are frequently detected in peripheral blood of patients harboring mutated primary tumors. As potential mechanism to explain the relative prevalence of wild type KRAS CTCs, 34 the generation of hypoxia in large advanced tumors or induced by treatments has been evoked.…”
Section: Discussionsupporting
confidence: 71%
“…1 In addition, initial primary tumor specimens are not always representative of the metastasis that can occur many years after the resection of the primary tumor. 2 After primary tumor biopsy or surgical removal, many other mutations can be acquired and other specific abnormalities found in the primary tumor can be lost. In this way, the CTC analysis can provide a non-invasive way of evaluating a tumor genotype and better correlate with the dynamic process of tumor progression and resistance to chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have shown that detection of KRAS mutations in the peripheral blood of mCRC patients is possible by the development of combining tests indicating in blood, first the presence of tumour DNA (circulating tumours cells), then KRAS status, with a highly significant correlation to KRAS mutations in tumours (Di Fiore et al, 2008;Yen et al, 2009). Moreover, it was reported in a series of 76 patients that those with KRAS wild-type circulating tumour cells had a better progression-free and overall survival when treated with cetuximab plus chemotherapy (Po0.0001) (Yen et al, 2009). These findings encourage to collect blood samples of mCRC patients to validate the clinical relevance of KRAS mutation detection in blood in future clinical trials with anti-EGFR monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%